Oxygen Therapy for Interstitial Lung Disease. A Mismatch between Patient Expectations and Experiences - Khor, Yet H.; Goh, Nicole S. L.; McDonald, Christine F.; Holland, Anne E. (Annals of the American Thoracic Society, 2017)
Domiciliary oxygen therapy is commonly prescribed for patients with interstitial lung disease and hypoxemia, either at rest or during exertion, with the aim of improving symptoms and functional status. This study aimed to explore perspectives of adults with interstitial lung disease about domiciliary oxygen therapy, comparing insights from patients using and not using oxygen therapy. A qualitative study using semistructured interviews was undertaken on 24 adults residing in and near Melbourne, Australia who had a diagnosis of interstitial lung disease and met the Thoracic Society of Australia and New Zealand guidelines for domiciliary oxygen therapy. Study subjects included individuals who were oxygen-naive (n = 12) and oxygen-experienced (n = 12). Interviews were transcribed verbatim and coded independently by two investigators in accordance with the grounded theory method of analysis. Themes were established by consensus. Patients using domiciliary oxygen therapy described widespread variation in usage. Oxygen-naive patients expected oxygen therapy to relieve dyspnea, whereas oxygen-experienced patients emphasized the benefits of oxygen on other, non-dyspnea-related physical symptoms. Practical and psychosocial challenges of using oxygen therapy were raised by both groups of patients. This study highlights the different expectations and experiences of domiciliary oxygen therapy for adults with interstitial lung disease. It is important to understand and address patients' concerns about the use of oxygen therapy for these patients.